R_IC: A novel and versatile implementation of the index of connectivity in R. (September 2022) - Martini, Lorenzo; Baggio, Tommaso; Torresani, Loris; Crema, Stefano; Cavalli, Marco
Abstract: Sediment connectivity is the capability of a system to regulate the exchange of sediment in catchments. The Index of Connectivity (IC) has become a widely used tool, offering a practical way to assess sediment connectivity from hillslopes to downstream channels. We present a novel implementation of IC in R environment to expand the audience of users and encourage alternative applications of the index. The R_IC is an open-source and freely available tool composed by three codes. Standard R_IC runs the IC and it represents the core of the other variants. Custom R_IC offers a more flexible script, allowing the computation of alternative weighting factors and the possibility of running a further profile IC analysis. Batch R_IC performs batch processing of the index. For each code variant, a geomorphological application is presented to illustrate how the R_IC could be used in watershed management and practical issues related to sediment dynamics. Highlights: The R_IC is a new tool computing the Index of Connectivity in R environment. The tool allows standard, custom and batch computations of the index. Application of R_IC is demonstrated in mountain catchments.